PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN DI KAWASAN WISATA ALAM AIK NYET KABUPATEN LOMBOK BARAT - Riki Kusuma Marga; Lalu Masyhudi; Ida Nyoman Tri Darma Putra; I Wayan Suteja; ulfan Mulyawan (Journal Of Responsible Tourism, 2022)
This study aims to determine the effect of service quality on tourist satisfaction in the natural tourism area of Aik Nyet, West Lombok Regency. This research is a quantitative research with service quality variables which include physical evidence, reliability, responsiveness, assurance and empathy as independent variables and tourist satisfaction as the dependent variable. The sample used was 100 respondents and the sampling technique used was simple random sampling. Data collection techniques using a questionnaire. The data analysis technique used is multiple linear regression with application SPSS version 25. The results of this study indicate that the variables of physical evidence, assurance and empathy partially have a significant influence on tourist satisfaction. The results of the t-test (partial) also show that the reliability and responsiveness variables do not have a significant effect on tourist satisfaction. Based on the results of the F (simultaneous) test, it shows that the service quality variable which includes physical evidence, reliability, responsiveness, assurance and empathy variables simultaneously has a significant influence on tourist satisfaction.